Implementasi Kebijakan Pengentasan Kemiskinan di Desa Molompar Kecamatan Tombatu Timur Kabupaten Minahasa Tenggara - Aprilita Laurentina Rogahang; Femmy Tulusan; NOVIE PALAR (JURNAL ADMINISTRASI PUBLIK, 2023)
the purpose of this study was to find out the Reality of Poverty Alleviation Policy Implementation in Molompar Village, East Tombatu District, Southeast Minahasa Regency. This study uses a qualitative method that is descriptive. In every formulation of a policy (program) is always accompanied by an implementation. Where Implementation is a series of activities in order to deliver policies to the community so that these policies can bring results as expected. Overall the implementation of poverty alleviation policies in Molompar Village, East Tombatu District, Southeast Minahasa Regency is still not good and not optimal based on research results obtained through observation data collection, interviews, and poverty alleviation policy documentation studies assessed using 4 indicators including Communication, resources, dispositions, and bureaucratic structures where there are still many people who do not want to use resources to innovate, in order to produce products or businesses, communication that still experiences errors every time implementing policies, bureaucratic structures that are still not efficient and the attitudes of policy implementers are lacking Good. Keywords : Implementation, Policy, Poverty